Parasitic Absorption and Internal Quantum Efficiency Measurements of Solid‐State Dye Sensitized Solar Cells. Issue 7 (5th April 2013) - Margulis, George Y.; Hardin, Brian E.; Ding, I‐Kang; Hoke, Eric T.; McGehee, Michael D.
Abstract The internal quantum efficiency (IQE) of solid‐state dye sensitized solar cells (ssDSCs) is measured using a hybrid optical modeling plus absorptance measurement approach which takes into account the parasitic absorption of the hole transport material (HTM). Across device thicknesses of 1 to 4 microns, ssDSCs sensitized with Z907 and TT1 dyes display relatively constant IQEs of approximately 88% and 36%, respectively, suggesting excellent charge collection efficiencies for both dyes but poor carrier injection for TT1 devices. The addition of more coadsorbent is shown to increase the IQE of TT1 up to approximately 58%, but significantly lowers dye loading. Finally, optical losses due to absorption by the HTM are quantified and found to be a significant contribution to photocurrent losses for ssDSCs sensitized with poor absorbers such as Z907, as the weak absorption of the dye gives the HTM opportunity for significant parasitic absorption within the active layer.